The Relationship Between Administrative Support and Teaching Performance of Non-Specialized Teachers in Public Junior High Schools in the Division of San Carlos City - Perez, MAEd, Roxette Ann G.; Marcellana, Rommel S. (Journal of Innovation in Education and Social Research, 2026)
This study assessed the relationship between administrative support and the teaching performance of non-specialized teachers in public junior high schools in the Division of San Carlos City, Negros Occidental. The study examined four specific areas of administrative support: mentoring, supervision, professional development, and resource provision, and their relationship to teaching performance metrics, including classroom management, teaching strategies, and assessment practices. The research employed a descriptive-correlational design and engaged 136 purposively selected non-specialized teachers from 13 public secondary schools during the academic year 2025–2026. Data were gathered using a validated Likert-type questionnaire and were analyzed through descriptive statistics and Pearson’s r to determine the relationship among the variables. The results indicated that administrative support was generally perceived as high, with supervision identified as the strongest domain. Teaching performance was also rated high, particularly in classroom management. A strong positive correlation was found between administrative support and teaching performance; however, the relationship was not statistically significant. This finding suggests that although administrative support coexists with high teaching performance, other factors may exert a greater influence on teaching outcomes among non-specialized teachers. Based on these results, a professional development plan was proposed to improve resource alignment, strengthen supervision, and enhance specialized training to better support non-specialized teachers in becoming more effective in the classroom.